2008
DOI: 10.1111/j.1365-2966.2008.13458.x
|View full text |Cite
|
Sign up to set email alerts
|

GD 552: a cataclysmic variable with a brown dwarf companion?

Abstract: GD 552 is a high proper motion star with the strong, double-peaked emission lines characteristic of the dwarf nova class of cataclysmic variable star, and yet no outburst has been detected during the past 12 years of monitoring. We present spectroscopy taken with the aim of detecting emission from the mass donor in this system. We fail to do so at a level which allows us to rule out the presence of a near-main-sequence star donor. Given GD 552's orbital period of 103 minutes, this suggests that it is either a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“… 1 Mackie (1920), 2 Thorstensen (2003), 3 Harrison et al (2004), 4 Augusteijn & Wisotzki (1997), 5 Abbott, Fleming & Pasquini (1997), 6 Gänsicke et al (2005), 7 Greenstein & Giclas (1978), 8 Unda‐Sanzana et al (2008), 9 Araujo‐Betancor et al (2005b), 10 Gänsicke et al (in preparation), 11 González (1983). …”
Section: Discussionmentioning
confidence: 99%
“… 1 Mackie (1920), 2 Thorstensen (2003), 3 Harrison et al (2004), 4 Augusteijn & Wisotzki (1997), 5 Abbott, Fleming & Pasquini (1997), 6 Gänsicke et al (2005), 7 Greenstein & Giclas (1978), 8 Unda‐Sanzana et al (2008), 9 Araujo‐Betancor et al (2005b), 10 Gänsicke et al (in preparation), 11 González (1983). …”
Section: Discussionmentioning
confidence: 99%
“…However, despite there are now more than 1400 CVs with an orbital period determination (Ritter & Kolb 2003), only a handful of period bouncer candidates have been so far identified (e.g. Patterson et al 2005b;Unda-Sanzana et al 2008;Littlefair et al 2006;Patterson 2011;Kato et al , 2016McAllister et al 2017;Neustroev et al 2017). Therefore the identification of additional period bouncers and the determination of their physical parameters is important for a direct comparison between the current models of CV evolution and observations in a region of the parameter space where very few objects are known.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that one of the systems has a very lowmass brown-dwarf companion by spectroscopic observations (Hernández Santisteban et al 2016). Unda-Sanzana et al (2008) found a CV which would have a brown-dwarf companion and a very low mass ratio. Aviles et al (2010) also detected a brown-dwarf binary with a likely small mass ratio.…”
Section: Introductionmentioning
confidence: 99%